Dynamic Proximal Ulnar Osteotomy for the Treatment of Ununited Anconeal Process in 17 Dogs - Turner, B. M.; Abercromby, R. H.; Innes, J.; McKee, W. M.; Ness, M. G. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
A prospective study was made of 17 dogs with ununited anconeal process treated by osteotomy of the proximal ulna. The effect of the surgery on lameness was evaluated subjectively and the elbows were assessed radiographically for evidence of anconeal fusion and healing of the osteotomy. Whilst clinical outcome was generally good and complications infrequent, relatively few cases achieved anconeal fusion. These results do not compare well with the results of a previous study but this disparity may be due in part to differences in patient population and radiographic evaluation.Further work is required to establish how best to achieve predictable anconeal fusion.Proximal ulnar osteotomy was used to treat 17 dogs with ununited anconeal process. Clinical results were good but anconeal fusion was not achieved consistently. Further work is needed to determine how best to achieve predictable anconeal fusion.
Keywords: Ununited anconeus; ulnar osteotomy